Effect of moon phases on dengue outbreaks in urban areas: A review - lyes, Makroui; Hj. Mohd. Noor, Norzailawati (Malaysian Public Health Physicians’ Association, 2016)
Dengue Fever (DF) is a flu-like viral infection with no current treatment. It is transmitted by Aedes aegypti and Aedes albopictus mosquito female bites; incubation takes 3-14 days. Dengue is an urban disease. Statistics show that more than 100 countries in 2014 were affected by DF. It is the result of the growing urban environment providing favourable breeding sites by man-made containers such as tires or uncollected refuse. Other factors such as weather temperature and rainfall are also influencing the mosquito life cycle. A research made suggested that there is a gap in research on determining the correlation between the biting habit of the vector and the moon phases. Therefore, this research is an attempt to analyse historical dengue cases reported by the Malaysian Ministry of Health and the moon phases for a period of five and a half years to establish a correlation between the two variables. More than 6000 data representing dengue cases were restructured to reflect the four moon phases. In the present study, it is being established that there is an increase in dengue cases during the new moon phase; this implies that there was a high landing rate three to 14 days earlier. This coincides with the full moon and the third quarter phases. The significance of these results would suggest that this temporal correlation is determinant on how the data should be gathered in the future. It will further strengthen the dengue surveillance by the relevant government agencies in Malaysia and the region.